(3GdefgGLs - (3YHO GdSdGe Hf YHO GdQMef Hf eMeO GddNej GdETHjdj, CHh GdMce,J (B536 (3g` s
(3ChdgG (B:s
(3PcQ TF ef eNJUQ CbGhjd GdfGS aj HOA GdNdb hPcQ HYV GdCfHjGA hGdNdaGA aj GdCQV s
(3BNQgG (B:s
(3YQafG Gddg JYGdi HQcGJg hNjQg Ke cJGH GdefgGLhcGf GdaQGZ efg YTjI jhe GdEKfjf (B29 (3QHjY GdChd YGe (B1295 (3ef gLQJg Udi Gddg Ydjg hSde hYdi Bdg hUMHg CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3ef U C (B2 - (3U H (B11s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B436 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B1428) s
Keywords: (3GdJGQjNs